Chromothripsis in Hodgkin lymphoma. Issue 8 (30th April 2013) - Nagel, Stefan; Meyer, Corinna; Quentmeier, Hilmar; Kaufmann, Maren; Drexler, Hans G.; MacLeod, Roderick A. F.
<x xml:space="preserve">Abstract</x> Chromosomal rearrangements are common features of most cancers, where they contribute to deregulated gene expression. Chromothripsis is a recently described oncogenic mechanism whereby small genomic pieces originating from one chromosomal region undergo massive rearrangements in a single step. Here, we document chromothripsis in Hodgkin lymphoma (HL) cell lines by genomic profiling, showing alternating amplicons of defined chromosomal regions. In L‐1236 cells, fluorescent in situ hybridization analyses identified aberrations affecting amplified chromosomal segments that derived from the long arm regions of chromosomes 3 and 9 and that colocalized to a derivative chromosome 6, indicating the cataclysmic origin of this mutation. The ABL1 gene at 9q34 was targeted by these rearrangements leading to its overexpression in L‐1236 cells, correlating with pharmacological resistance to treatment with the kinase inhibitor dasatinib. Collectively, we identified and characterized chromothriptic rearrangements in HL cell lines to serve as models for analyzing this novel oncogenomic mechanism. © 2013 Wiley Periodicals, Inc.